CHANGES IN CARDIORESPIRATORY INDICATORS IN THE DEVELOPMENT OF METABOLIC SYNDROME DUE TO PHYSICAL EXERCISES (Global Conference on Medical and Health Sciences, 2026)
Over the past decade, the prevalence of metabolic syndrome among the population has been increasing, and it is considered one of the factors posing a serious threat to global health. Metabolic syndrome is formed under the influence of interrelated risk factors such as obesity, insulin resistance, arterial hypertension, and dyslipidemia, as well as a sedentary lifestyle and irregular eating habits. Genetic predisposition exacerbates the negative impact of behavioral factors, leading to the development of metabolic disorders. This article is aimed at preventing the development of metabolic syndrome by assessing cardiorespiratory parameters in certain sports under the influence of physical loads.
Keywords: Heart rate, systolic pressure, diastolic pressure, physical load, metabolic syndrome.